2022
DOI: 10.3389/fonc.2022.829777
|View full text |Cite
|
Sign up to set email alerts
|

HAUS5 Is A Potential Prognostic Biomarker With Functional Significance in Breast Cancer

Abstract: BackgroundBreast cancer (BRCA) has become the most frequently appearing, lethal, and aggressive cancer with increasing morbidity and mortality. Previously, it was discovered that the HAUS5 protein is involved in centrosome integrity, spindle assembly, and the completion of the cytoplasmic division process during mitosis. By encouraging chromosome misdivision and aneuploidy, HAUS5 has the potential to cause cancer. The significance of HAUS5 in BRCA and the relationship between its expression and clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…As shown in Fig. 1 C, HAUS5 mRNA levels were significantly higher in glioblastoma (GBM) 17 , brain lower grade glioma (LGG), lung adenocarcinoma (LUAD), colon adenocarcinoma (COAD), breast invasive carcinoma (BRCA) 16 , esophageal carcinoma (ESCA), kidney renal papillary cell carcinoma (KIRP), stomach adenocarcinoma (STAD), prostate adenocarcinoma (PRAD), uterine corpus endometrial carcinoma (UCEC), head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), lung squamous cell carcinoma (LUSC), LIHC, thyroid carcinoma (THCA), rectum adenocarcinoma (READ), bladder urothelial carcinoma (BLCA) and cholangiocarcinoma (CHOL) tissues than in normal tissues. Due to the small normal sample size of some cancers, we integrated the GTEx and TCGA datasets with log2(x + 1) expression value and analyzed the differences of HAUS5 expression in 27 cancer types.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…As shown in Fig. 1 C, HAUS5 mRNA levels were significantly higher in glioblastoma (GBM) 17 , brain lower grade glioma (LGG), lung adenocarcinoma (LUAD), colon adenocarcinoma (COAD), breast invasive carcinoma (BRCA) 16 , esophageal carcinoma (ESCA), kidney renal papillary cell carcinoma (KIRP), stomach adenocarcinoma (STAD), prostate adenocarcinoma (PRAD), uterine corpus endometrial carcinoma (UCEC), head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), lung squamous cell carcinoma (LUSC), LIHC, thyroid carcinoma (THCA), rectum adenocarcinoma (READ), bladder urothelial carcinoma (BLCA) and cholangiocarcinoma (CHOL) tissues than in normal tissues. Due to the small normal sample size of some cancers, we integrated the GTEx and TCGA datasets with log2(x + 1) expression value and analyzed the differences of HAUS5 expression in 27 cancer types.…”
Section: Resultsmentioning
confidence: 81%
“…Although it is known the augmin complex plays an important role in the correct assembly of the spindle, few studies have been conducted on HAUS5. A recent study suggested that HAUS5 is a potential biomarker in breast cancer 16 . However, the role of HAUS5 in hepatocellular carcinoma remains unknown and deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the potential biological function and pathway, we frst screened the DEGs between the low-and high-PTPN1 expression groups using the R package "limma." Te genes with log 2 |fold change (FC)| larger than one and adjusted p value (q value) lower than 0.05 were considered signifcant DEGs [14]. Next, these DEGs were used to perform GO and KEGG pathway enrichment analysis.…”
Section: Gene Function and Pathway Analysis By Go Kegg Andmentioning
confidence: 99%
“…Next, these DEGs were used to perform GO and KEGG pathway enrichment analysis. GO terms and KEGG pathways with q value lower than 0.05 were signifcantly enriched in DEGs [14]. Furthermore, we also utilized GSEA pathway analysis on PTPN1 by the KEGG gene sets.…”
Section: Gene Function and Pathway Analysis By Go Kegg Andmentioning
confidence: 99%
See 1 more Smart Citation